PENAPISAN VIRTUAL SENYAWA TURUNAN METIL SINAMAT PADA ENZIM SIKLOOKSIGENASE-2 (COX-2 - Teni Ernawati (Jurnal Kimia Terapan Indonesia, 2012)
Inflammation is the response of living tissue to vascular injury. Non-Steroid Anti-Inflammatory Drugs(NSAIDs)  could  control  pain  caused  by  inflammation.  Therapeutic  effects  of  NSAIDs  are  related  to  themechanism of the cyclooxygenase-1 (COX-1) enzyme and the cyclooxygenase-2 (COX-2) enzyme in inhibiting theproduction of prostaglandins. In this paper, we report the virtual screening of methyl cinnamate derivativecompounds against the COX-2. All methyl cinnamate derivative compounds were  molecular docking simulatedusing the Protein-Ligand ANT System (PLANTS) software with  ZINC03814717 as the reference compound. Fromthe results of virtual screening, it was obtained that  derivative compounds of methyl cinnamate were predicted asactive  COX-2  inhibitors  because  they  have  ChemPLP  score  better  than  that  of  the  reference  compoundsZINC03814717. The compound of acid 3- (4-benzoylphenyl) propionate was predicted as having the best score ofChemPLP.Keywords:  Non-Steroid Anti-Inflammatory (NSAID), virtual screening, enzyme cyclooxygenase-2 (COX-2), methyl cinnamate derivative